Time division multiplexing based multiple synchronised chaotic signals transmission. Issue 1 (1st January 2013) - Han, F.; Feng, Y.; Qi, C.
Abstract : Presented is a method of transmitting multiple synchronised chaotic signals via a single channel based on time division multiplexing. Both the sampling and holding modes are used alternately during the transmission process so that multiple chaotic signals can be transmitted by sharing the single physical channel. The proposed method is implemented with an electronic circuit, and then is applied to solve simultaneous synchronisation of multi‐pair chaotic systems using a single channel. Experimental results show the effectiveness of the method presented.